Struktura semantyczna słów nazywających uczucia - Wierzbicka, Anna (Poznańskie Studia Polonistyczne. Seria Literacka, 2019)
Based on the analysis of Leo Tolstoy’s novel Anna Karenina, the article deals with semantic structure of words for emotions.